Screening algorithm for predementia cognitive impairment in cardiovascular patients at a general practitioner's appointment. Expert Consensus Statement - O. M. Drapkina; S. A. Berns; S. Yu. Nikulina; E. Yu. Solovieva (Кардиоваскулярная терапия и профилактика, 2024)
.